Does Digital Marketing Impact Student Enrollment At Universitas Buana Perjuangan Karawang? - Muhammad Abi Dzar; Dini Yani; Rieke Retnosary (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to explore the impact of Instagram usage among management students who were enrolling at Universitas Buana Perjuangan Karawang in 2023. The study examines students' experiences and perceptions of the university's official Instagram account using a quantitative descriptive approach based on multiple linear regression analysis. The research reveals that management students of the 2023 intake highly prefer Universitas Buana Perjuangan Karawang over other universities. Additionally, the study shows the positive impact of Social Media Instagram and digital marketing strategies in influencing students' decision-making processes. The enrollment of management students at Universitas Buana Perjuangan Karawang for the 2023 intake increased impact by implementing Instagram as a marketing strategy.